Vaižgantas in Lithuanian Schools - Vanagaitė, Gitana (Colloquia, 2021)
The author of the article examines the representation of Juozas Tumas - Vaižgantas’s biography and works in gymnasium literature curricula and textbooks from 1916 to the present day. The focus is on the canonical short story “Dėdės ir dėdienės” [Uncles and Aunts], highlighting its place in gymnasium literature curricula and the semantic-interpretive points of reference in literature textbooks. The research had revealed that Vaižgantas was included in gymnasium literature curricula in the second decade of independence of Lithuania, when the state was already being established and the opportunities for the creation of a national education system opened up. The gymnasium curricula in interwar Lithuania included a number works by Vaižgantas: extracts from “Pragiedruliai” [Cloud Clearing], impressions, journalistic articles, and fragments of the short story “Uncles and Aunts.” Vaižgantas’s stories were studied in lower and upper grades. Only starting in 2002, they were no longer part of the lower secondary school curricula. Even before World War I, excerpts from Vaižgantas’s works entered various reading books (earlier than gymnasium curricula). Soon after the publication of author’s main works, “Cloud Clearing” and “Uncles and Aunts,” Vaižgantas was added in school curricula as an important 20th century Lithuanian author. His reception in literary science and Lithuanian school went hand in hand, as the major academic studies of Vaižgantas’s works appeared after his death. Undoubtedly, the school played the role of preserving or memorializing Vaižgantas’s life and works, and to some extent began the process of canonizing his oeuvre. The ideologies of different political periods led to distinct idea- and value-based points of reference for reading the Vaižgantas’s biography and works, which prevented the creation of a solid approach to perception and interpretation of his oeuvre that was binding on the canon. The obligatory ideological interpretation in the Soviet period overshadowed the aesthetic dimension of writer’s works; even though it was this dimension that had guaranteed constant renewal and change of Vaižgantas’s works in the literary canon.